Neuroaxial anesthesia caused paraplegia: a case report - Cortés-Badillo, Luis David; Reyes-Gutiérrez, Agustín; Gómez-Chaccón, Óscar; Olivera-León, Luis David; Olivera-León, Elsy Daniela; Granados-Romero, Juan José; Barrera-Mera, Baltazar; Banegas-Ruiz, Rodrigo; Vargas-Morales, José Juan; Barrera-Calva, Elvira; Gómez-Mendoza, Francisco Fabián; Baca-Domínguez, Carlos Rubén; et al. (International Journal of Research in Medical Sciences, 2021)
Patients who undergo; anesthesia, neuraxial analgesia, or some type of neuraxial blockage are exposed to multiple complications. 33-year-old male patient, suffers a femur fracture with a long oblique trace causing pain and functional limitation for movements. Surgical resolution is determined using neuraxial block at L2-L3 level, and intravenous sedation. During his postoperative follow-up, a decrease in strength was confirmed in the lower limbs with 0/5 on the Daniels scale, 100% sensitivity without sphincter control, steroids were prescribed along with magnetic resonance imaging and a neurosurgical evaluation was requested. The MRI shows bulging of the fibrous annulus that obliterates the epidural fat and makes contact with the thecal sac in the L5-S1 intervertebral disc level. The neurosurgery service prescribes rehabilitation sessions at home, electrostimulation and neuropathic medications. Patient was discharged with rehabilitation sessions at home and medical treatment. In his last consultation, an evaluation from the psychiatry department was requested for ideas of disability, hopelessness, fantasies of death without a suicide plan related to limitations and loss of functionality. Patient does not return to external follow-up, cannot be located.